ADSORPTION OF As(III) FROM AQUEOUS SOLUTION ONTO IRON IMPREGNATED USED TEA ACTIVATED CARBON: EQUILIBRIUM, KINETIC AND THERMODYNAMIC STUDY - Mahmood, Tahira; Aslam, Madeeha; Naeem, Abdul; Siddique, Tahir; Din, Salah Ud. (Journal of the Chilean Chemical Society, 2018)
An efficient and cost effective adsorbent, activated carbon (UTAC) derived from used tea (UT) for the removal of As(III) from aqueous solutions was developed. To increase adsorption, UTAC was then impregnated with (magnetite) iron oxide particles (Fe-UTAC). The prepared adsorbents were characterized by XRD, SEM/EDX, FTIR and surface area analyzer. A comprehensive kinetic study of arsenite adsorption onto Fe-UTAC was conducted at 298-318 K and pH 8. The Richenberg model confirmed film diffusion to be the main rate limiting step. The removal of As(III) from aqueous solution onto Fe-UTAC was carried out as a function of temperature, concentration and pH. The sorption capacity (mol g-1) of Fe-UTAC was observed to increase with increase in arsenite concentration while a decrease in the As(III) uptake was observed by increasing the temperature of the system. The sorption capacity of Fe-UTAC was almost three and six times larger than that of UTAC and UT respectively. The effect of pH on the arsenite adsorption was significant in the pH range 7–8 which may be correlated with the stability of Fe-UTAC as no release of iron from Fe-UTAC was observed. The mean free energy calculated from DR mechanism confirmed adsorption to be chemisorption and followed ligand exchange mechanism. The thermodynamic parameters confirmed adsorption to be exothermic, spontaneous and favorable.